The GUIDE-HF trial of pulmonary artery pressure monitoring in heart failure: impact of the COVID-19 pandemic. (10th March 2022) - Zile, Michael R; Desai, Akshay S; Costanzo, Maria Rosa; Ducharme, Anique; Maisel, Alan; Mehra, Mandeep R; Paul, Sara; Sears, Samuel F; Smart, Frank; Chien, Christopher; Guha, Ashrith; Guichard, Jason L; et al.
Abstract: Aims: During the coronavirus disease 2019 (COVID-19) pandemic, important changes in heart failure (HF) event rates have been widely reported, but few data address potential causes for these changes; several possibilities were examined in the GUIDE-HF study. Methods and results: From 15 March 2018 to 20 December 2019, patients were randomized to haemodynamic-guided management (treatment) vs. control for 12 months, with a primary endpoint of all-cause mortality plus HF events. Pre-COVID-19, the primary endpoint rate was 0.553 vs. 0.682 events/patient-year in the treatment vs. control group [hazard ratio (HR) 0.81, P  = 0.049]. Treatment difference was no longer evident during COVID-19 (HR 1.11, P  = 0.526), with a 21% decrease in the control group (0.536 events/patient-year) and no change in the treatment group (0.597 events/patient-year). Data reflecting provider-, disease-, and patient-dependent factors that might change the primary endpoint rate during COVID-19 were examined. Subject contact frequency was similar in the treatment vs. control group before and during COVID-19. During COVID-19, the monthly rate of medication changes fell 19.2% in the treatment vs. 10.7% in the control group to levels not different between groups ( P  = 0.362). COVID-19 was infrequent and not different between groups. Pulmonary artery pressure area under the curve decreased −98 mmHg-days in the treatment group vs. −100 mmHg-days in the controls ( P  = 0.867). Patient compliance with the study protocol was maintained during COVID-19 in both groups. Conclusion: During COVID-19, the primary event rate decreased in the controls and remained low in the treatment group, resulting in an effacement of group differences that were present pre-COVID-19. These outcomes did not result from changes in provider- or disease-dependent factors; pulmonary artery pressure decreased despite fewer medication changes, suggesting that patient-dependent factors played an important role in these outcomes. Clinical Trials.gov: NCT03387813 Structured Graphical Abstract: Structured Graphical Abstract Patient-dependent factors played an important role in the outcomes of GUIDE-HF.